Effective Treatments for Auditory Sensitivities in Autism - Chenausky, MS, CCC-SLP, Karen (North American Journal of Medicine and Science, 2011)
Hypersensitivity to sound is a frequent symptom of autism spectrum disorders and can be difficult to manage. Because an individual with sound hypersensitivity may display disruptive behaviors for significant periods of time in response to the sound, the condition demands treatment. Behavioral and desensitization therapies, which employ some of the techniques of cognitive behavioral therapy, appear to be promising, efficient, and effective types of treatment for these symptoms.